Problem of Brain Injury during Cardiosurgical Interventions Under Extracorporeal Circulation - V. V. Moroz; A. I. Korniyenko; A. S. Mozalev; A. V. Parfenyuk; S. V. Shakhmayeva (Общая реаниматология)
The paper analyzes today’s concepts on the causes of cerebral dysfunction at surgery under extracorporeal circulation. It considers the medical measures promoting the prevention of brain lesion and the ways of working out new cerebral protective strategies. Key words: psychoneurological complications, extracorporeal circulation.